Evaluación de Parámetros Hematológicos del Búfalo de Agua (bubalus bubalis) de la Empresa Palmicultora Palmar del Río en la Región Amazónica. - Montesdeoca Arellano, Gardeña Lucrecia (2020)
The present research, titled ``Evaluation of Hematological Parameters of Water Buffalo (Bubalus Bubalis) from the `Palmar Del Rio Palm Grower Company in the Amazon Region´´, aims to evaluate the behavior of biometric and biochemical values of the animals in the study region, and the comparison with trust sources that show real problems data in our country. Twenty-eight samples of animals, distributed according age and sex, were processed and the results were analyzed using T from one variable. T student was used in the evaluation by sex for general parameters of biometry and biochemistry; for the age variable an ADEVA with a Factorial Complete Random Design (DCA) with the statistical difference Duncan 0. 05% in the INFOSTAT statistical system, we can determine a average of Biometry parameters describing Hematocrit 41,31±0,89 %, Hemoglobin 14,53±0,35 g/L, Average cell hemoglobin concentration 35.14±0.2 g/dL, Leukocytes 5.31±0.15 K/µL, Granulocytes 2.13±0.14 %, Lymphocytes 3.19±0.17 x10 ^9/L, %, Platelets 207.89±8.11 K/μL. In the biochemistry parameters we got: Glucose 57.14± 2.07 mg/dL, Creatinine 1.66± 0.09 mg/dL, Blood Urea Nitrogen 11.07± 0.47 mg/dL, BUN/Creatinine ratio 7.07± 0.25, Total Protein 9.18± 0.31 mg/dL, Albumin 3.29± 0.08 mg/dL, Globulin 5.87± 0.25 mg/dL, Albumin/Globulin ratio 0.58± 0.03, Alanine aminotransferase 86.5± 4.97 U/L, Alkaline phosphatase 250.79± 33.03 U/L. By comparing, it was obtained that the parameters were in relation with another researches. The present research show new values of biometric and biochemical parameters that serve as reference; Granulocytes 2.13±0.14 K/μ, Glucose 57.14± 2.07mg/dL, Blood Ureic Nitrogen 11.07± 0.47 mg/dL, BUN/Creatinine ratio 7.07± 0.25, Alanine aminotransferase 86.5± 4.97 U/L.